Annual plant reviews, Volume 30: Light and Plant Development - Whitelam, Garry C (Blackwell, 2012)
Living organisms are subject to fluctuating environmental conditions. Whereas most animals are able to move away from unfavourable conditions, plants are sessile and so must cope with whatever comes their way. Of all the environmental cues that challenge the developing plant, light can probably be considered to be the most important. In addition to its key role in plant metabolism, and hence almost all life on Earth, where it drives the process of photosynthesis, light energy also acts to regulate plant growth and development. Light quantity, quality, direction and diurnal and seasonal duratio.